ACTIVITIES IN SOLID AND LIQUID FE-NI AND FE-CO ALLOYS DETERMINED BY KNUDSEN CELL MASS-SPECTROMETRY - Rammensee, W; Fraser, D (1981)
The thermodynamic activities and heats of mixing of liquid and solid solutions in the systems Fe-Ni and Fe-Co have been measured by Knudsen-Cell mass spectrometry using a newly designed molecular beam apparatus. The data obtained for the system Fe-Ni agree very closely with previous results and conform negative deviations over the whole concentration range. Results for Fe-Co indicate negative deviations from ideality for all compositions between X//C//o equals 0. 05-1. 00 and positive deviations below X//C//o equals 0. 05. This supports calorimetric measurements and is in conflict with a previous mass-spectrometric investigation reporting positive deviations from ideality.